Interaction between chicken TRIM25 and MDA5 and their role in mediated antiviral activity against IBDV infection - Diaz-Beneitez, Elisabet; Cubas-Gaona, Liliana Lilibeth; Candelas-Rivera, Oscar; Benito-Zafra, Ana; Sánchez-Aparicio, Maria Teresa; Miorin, Lisa; Rodríguez, José F.; García-Sastre, Adolfo; Rodríguez, Dolores (Frontiers in Microbiology, 2022)
Infectious Bursal Disease Virus (IBDV) is the causative agent of an immunosuppressive disease that affects domestic chickens (Gallus gallus) severely affecting poultry industry worldwide. IBDV infection is characterized by a rapid depletion of the bursal B cell population by apoptosis and the atrophy of this chief lymphoid organ. Previous results from our laboratory have shown that exposure of infected cells to type I IFN leads to an exacerbated apoptosis, indicating an important role of IFN in IBDV pathogenesis. It has been described that recognition of the dsRNA IBDV genome by MDA5, the only known cytoplasmic pattern recognition receptor for viral RNA in chickens, leads to type I IFN production. Here, we confirm that TRIM25, an E3 ubiquitin ligase that leads to RIG-I activation in mammalian cells, significantly contributes to positively regulate MDA5-mediated activation of the IFN-inducing pathway in chicken DF-1 cells. Ectopic expression of chTRIM25 together with chMDA5 or a deletion mutant version exclusively harboring the CARD domains (chMDA5 2CARD) enhances IFN-β and NF-ĸB promoter activation. Using co-immunoprecipitation assays, we show that chMDA5 interacts with chTRIM25 through the CARD domains. Moreover, chTRIM25 co-localizes with both chMDA5 and chMDA5 2CARD, but not with chMDA5 mutant proteins partially or totally lacking these domains. On the other hand, ablation of endogenous chTRIM25 expression reduces chMDA5-induced IFN-β and NF-ĸB promoter activation. Interestingly, ectopic expression of either wild-type chTRIM25, or a mutant version (chTRIM25 C59S/C62S) lacking the E3 ubiquitin ligase activity, restores the co-stimulatory effect of chMDA5 in chTRIM25 knockout cells, suggesting that the E3-ubiquitin ligase activity of chTRIM25 is not required for its downstream IFN-β and NF-ĸB activating function. Also, IBDV-induced expression of IFN-β, Mx and OAS genes was reduced in chTRIM25 knockout as compared to wild-type cells, hence contributing to the enhancement of IBDV replication. Enhanced permissiveness to replication of other viruses, such as avian reovirus, Newcastle disease virus and vesicular stomatitis virus was also observed in chTRIM25 knockout cells. Additionally, chTRIM25 knockout also results in reduced MAVS-induced IFN-β promoter stimulation. Nonetheless, similarly to its mammalian counterpart, chTRIM25 overexpression in wild-type DF-1 cells causes the degradation of ectopically expressed chMAVS.